2023
DOI: 10.1101/2023.07.06.548010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Helicity of a tardigrade disordered protein promotes desiccation tolerance

Abstract: In order to survive extreme drying (anhydrobiosis), many organisms, spanning every kingdom of life, accumulate intrinsically disordered proteins (IDPs). For decades, the ability of anhydrobiosis-related IDPs to form transient amphipathic helices has been suggested to be important for promoting desiccation tolerance. However, evidence empirically supporting the necessity and/or sufficiency of helicity in mediating anhydrobiosis is lacking. Here we demonstrate that the linker region of CAHS D, a desiccation-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 75 publications
(113 reference statements)
2
0
0
Order By: Relevance
“…Interestingly, CAHS1M1 adopts mainly a helical configuration already at 0 % TFE. Upon mimicking desiccation (either by adding TFE or by exposing the peptides to a water/air interface), we observed that all model peptides adopt helical structures, similar to what is observed for the entire protein (5,15). The control peptide, however, does not show any tendency to form a helical structure, only a slightly more propensity to bend.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Interestingly, CAHS1M1 adopts mainly a helical configuration already at 0 % TFE. Upon mimicking desiccation (either by adding TFE or by exposing the peptides to a water/air interface), we observed that all model peptides adopt helical structures, similar to what is observed for the entire protein (5,15). The control peptide, however, does not show any tendency to form a helical structure, only a slightly more propensity to bend.…”
Section: Discussionsupporting
confidence: 76%
“…We note that the control peptide, expected to have different physicochemical properties, has a more ordered structure, consisting of a bend/turn that is stabilized under drying conditions. Furthermore, sequence-structure analysis suggests that specific patterns in the sequence, such as alternating of positive and negative charges, might be crucial in stabilizing alpha-helical conformations, as suggested in literature (15,16). Finally, our observations indicate that the four model peptides not only exhibit surface activity but also, consistent with bulk findings, adopt a helical structure under partially dehydrated conditions, suggesting that this conformation is the most preferred in these circumstances.…”
Section: Introductionsupporting
confidence: 83%